The Development of Construction Service Marketplace System using Laravel Framework - Mohd Isamani, Maisa Damia; Mohd Zin, Nur Ariffin (Applied Information Technology And Computer Science, 2022)
Many local consulting firms and contractors struggle to engage and have better communication with clients or vice versa. This struggle may or may not cause work overload and difficulty to maintain client relationships. Hence, this study proposes developing a construction services marketplace system where clients and service providers can interact on a single platform. This study has initiated a collaboration with a construction consultant company named TrisM Kontrak Sdn Bhd that addresses the associated issue by integrating the current practice with modern technology and cloud computing architecture.